Enhancing productivity of rice (Oryza sativa)-rice-fallow system through balanced fertilization: A farmer participatory approach in Kerala’s southern coastal plains - JACOB, D; PARAMESHA, V; BINDHU, J S; MEERA, A V; INNAZENT, ANITROSA (The Indian Journal of Agricultural Sciences, 2025)
A farmer participatory approach captures diverse farming practices in their environmental context, generating locally appropriate solutions to address challenges. The present experiment, conducted during rainy (kharif) and winter (rabi) seasons from 2017–18 to 2022–23 in six panchayats of Thiruvananthapuram, Kerala was aimed to evaluate the effects of balanced NPK fertilization, including ZnSO4, on the productivity and profitability of the rice (Oryza sativa L.)-rice-fallow system in Kerala’s southern coastal plains, with a focus on farmer participation and site specific nutrient management. The experiment was laid out in a randomized block design (RBD) with 7 treatments, viz. T1, Control (no fertilization); T2, N; T3, NP; T4, NK; T5, NPK; T6, NPK + ZnSO4; and T7, Conventional farmers’ practice (FP), with rice (Oryza sativa L.) grown in both rainy (kharif) and winter (rabi) seasons. The application of balanced fertilization NPK + ZnSO4 (NPK 90:45:45 kg/ha + ZnSO4 20 kg/ha in kharif and NPK 90:45:45 kg/ha in rabi) to medium duration rice significantly increased system rice equivalent yield (5.25 t/ha and 5.20 t/ha) in both seasons. The highest system rice equivalent yield (10.46 t/ha), gross return (₹2.92 lakh/ha), net return (₹0.89 lakh/ha) and benefit cost ratio (1.44) were recorded with NPK+ ZnSO4. In addition to improved nutrient response (26.28 kg yield/ kg nutrient), higher sustainable value index (0.71) was observed with NPK + ZnSO4. The farmer participatory study concluded that balanced fertilization with NPK + ZnSO4 is essential for increased rice yield, system productivity, and economic profitability in the rice-rice-fallow system. The successful farmer adoption of this balanced fertilization highlights the need for policy support to promote development of location specific sustainable agricultural systems.